The Use of Authentic Materials to Enhance Speaking Skills among ESL Learners at a Public Community College in Sabah, Malaysia: a Proposal - Karen Chong Mei Teng; Asmaa AlSaqqaf (Proceedings International Conference on Teaching and Education (ICoTE), 2022)
In the world of globalisation advancement, the role of the English language is greatly accentuated in the Malaysian education system. The capability to speak English is a prevailing tool in getting all offered fields a success. Despite the formal learning of English over years at school, Malaysian learners are still unable to achieve a desirable competency level of English proficiency. The current situation of the Malaysian ESL school learners imposed a great obstacle which affects them tremendously by being incompetent in communicating English. Very limited research has been done to address the speaking problems among Sabah’s community college ESL learners. Ideally, the usage of authentic materials should help learners to speak. This study attempts to reduce this gap by embarking on the intervention to use authentic materials for teachers to teach speaking skills. This study is going to apply a mixed-method approach and quasi-experimental design. Experimental group students will be receiving an authentic materials module for 14-weeks, while control group students will be receiving traditional method teaching. A pre-test and post-test will be conducted to identify that there’s no significant difference in the mean score between the two groups of participants before and after the intervention. It is hoped that the results of this study would contribute to improving the speaking skill among Community College students.